Ablation of striatal somatostatin interneurons affects MSN morphology and electrophysiological properties, and increases cocaine‐induced hyperlocomotion in mice. (14th October 2019) - Gazan, Adeline; Rial, Daniel; Schiffmann, Serge N.
Abstract: The striatum is mainly composed by medium spiny neurons (95 %) (MSNs). Although outnumbered, in other brain regions such as the hippocampus and the cortex, somatostatin interneurons (SSTi) are known to control and fine‐tune the activity of principal cells. This information is still fragmented for the striatum. Here, we questioned the striatal functional consequences of the selective ablation of SSTi in the striatum at the behavioural and cellular levels. We identified increased excitability coupled with decreased distal spine density in MSNs from SSTi‐ablated mice. Although the ethological behavioural analysis did not reveal differences between the groups, SSTi‐ablated mice were significantly more sensitive to the locomotor effects of cocaine without changes in motivation. This was accompanied by increased expression of the dopamine transporter (DAT) in the ventral striatum. Altogether, we show that SSTi are important players in the maintenance of MSN excitability and spine density impacting on mechanisms towards hyperdopaminergic states. Abstract : In this study, we evaluate the role of somatostatin interneurons in the striatal physiology. Overall, we show that somatostatin interneurons play an important role in the maintenance of medium spiny neurons excitability and spine density, thus causing an impact on mechanisms towards hyperdopaminergic states.